Family Roles of Roma and Ways to Overcome its Socio-Cultural Isolation - Afanasieva, Lyudmila; Bukrieieva, Iryna; Glyns’ka, Lyudmila; Hlebova, Natalia Ivanivna; Semikin, Mykhailo (Journal of History Culture and Art Research, 2020)
The cultural factor has always played an important role in the lives of peoples. The ethnic specificity of life developed over the centuries has been embodied in customs, language, family traditions, consciousness, psychology, and character. Their formation and development have always been accompanied by a significant transformation of stereotypes in the minds of a particular society. Accompanying on the whole path of socio-cultural development, ethnic stereotypes are passed from generation to generation, becoming an element of ethnic consciousness in family relationships. Gender stereotypes are closely linked to gender roles. The formation and regulation of state policy on gender equality are carried out in accordance with the international obligations and legislation of each state. The differences in gender roles depend on the degree of masculinity or femininity of a culture. Each ethnic group has its own socio-cultural role adaptation to the family life. Different ethnic cultures have their own stereotypes about the family responsibilities of husband and wife, and marital relationships have national specifics. It is especially true of such a non-territorial nation, which is as widespread around the world as the Roma. The traditionalism and conservatism of their gender stereotypes hinder socialization and self-realization, especially for women who suffer from double discrimination on the basis of ethnicity and gender. Gender inequality and discrimination against Roma women remained an acute problem in various spheres of life and in the family in particular at the beginning of the third millennium. And since the Roma are a fairly closed ethnic group, the shifts in their consciousness of women’s and men’s roles and relationships are changing rather slowly. Consideration and comprehension of the essence of gender roles and stereotypes in relation to Roma woman, on the example of research by Ukrainian scholars, will allow to analyze the causes and consequences of gender issues of Roma, which also exist in other countries, and also, to offer the mechanisms for overcoming the negative phenomena and the ways of forming gender family relations of Roma, which are based on the idea of social equality and justice, stability of Roma woman self-realization, opportunities to live a full life based on their closed environment.